Niger : Third Review Under the Poverty Reduction and Growth Facility Arrangement and Requests for Modification and Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper evaluates Niger's Third Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement and Requests for Modification and Waiver of Performance Criteria. Performance under the program at end-December 2001 was broadly satisfactory, despite delays in foreign assistance disbursements and recurring weaknesses in program implementation owing to limited institutional capacity. At end-December 2001, eight of the eleven quantitative and structural benchmarks were met. The program remained on track at end-March 2002 as the authorities took expenditure-reducing measures to correct for budgetary slippages that occurred in the last quarter of 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet